HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN DAYA JUANG DENGAN ORIENTASI WIRAUSAHA PADA MAHASISWA PROGRAM PROFESI APOTEKER UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - Susanti, Novita (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstractThis study aimed to determine the relationship between social support and power struggle with entrepreneurial orientation. As for the study was conducted on students of the Faculty of Pharmacy, University Professions Pharmacists Ahmad Dahlan Yogyakarta academic year 2012/2013 with a sample of the study by 75 students who have never had a business or businesses. Data collection tool using three scales are scales entrepreneurial orientation, social support scale and the scale of the power struggle. The technique of sampling using incidental sampling. The method of data analysis is the technique of multiple regression analysis were analyzed using SPSS 15.0 for Windows Evaluation Version. The results of the analysis of data obtained correlation coefficient R = 0.377 with a p = 0.004 (p < 0.05), the correlation coefficient rx1y = 0.226 and p = 0.026 (p < 0.05) and rx2y of 0.365 with p = 0.001 (p < 0. 05). Based on these results, we can conclude that there is a significant positive relationship between social support and power struggle with an entrepreneurial orientation, the higher the social support and power struggle then the higher the entrepreneurial orientation. The effective contribution of social support and power struggle of the entrepreneurial orientation of 14.2% while the remaining 85.8% contributed by other factors such as personality factors, the environment, demographics (age, gender) and other factors.Â Key words: social support, power struggle and entrepreneurial orientation